Treatment and outcome of non-tuberculous mycobacterial pulmonary disease in a predominantly fibro-cavitary disease cohort. (October 2017) - Zweijpfenning, Sanne; Kops, Stephan; Magis-Escurra, Cecile; Boeree, Martin J.; van Ingen, Jakko; Hoefsloot, Wouter
Abstract: Background: The incidence of non-tuberculous mycobacterial pulmonary disease (NTM-PD) has increased in the Netherlands. The fibro-cavitary disease manifestation predominates, as elsewhere in Europe. We studied treatment and outcome of this disease manifestation, as such data are scarce. Methods: We conducted a retrospective study of all patients diagnosed with NTM-PD according to the American Thoracic Society statement between 2008 and 2013 in a reference clinic. Results: Sixty-three patients were included. Thirty-two (51%) were females and mean age was 60.8 years. Most patients had underlying COPD (73%). M. avium complex pulmonary disease (MAC-PD) was most frequent (n = 38, 60.3%), followed by M. malmoense (n = 7) and M. kansasii (n = 6). Twenty-two patients had fibro-cavitary MAC-PD, 14 had nodular-bronchiectatic MAC-PD and 2 had other manifestations. Thirty-two (94%) patients treated for MAC-PD received a rifamycin-ethambutol-macrolide based regimen. Microbiological cure rates were lower for fibro-cavitary (52.4%) than for nodular bronchiectatic MAC-PD (100%; p = 0.03). Sixty-nine percent of treated patients experienced adverse events, most frequently gastrointestinal discomforts (71%), tinnitus (18%), hearing impairment (16%) and hepatotoxicity (18%). Conclusions: Fibro-cavitary NTM-PD remains predominant, but is now diagnosed more frequently in women. Fibro-cavitary disease is harder to cure than nodular-bronchiectatic disease. Adverse events are frequent and can necessitate cessation of treatment. Highlights: Predominantly fibrocavitary NTM pulmonary disease. Increasing prevalence of nodular-bronchiectatic MAC-PD. Lower Cure rates in fibro-cavitary vs. nodular bronchiectatic MAC-PD. Toxicity is problematic and can necessitate cessation of therapy.